Newark : a History of Race, Rights, and Riots in America. - Mumford, Kevin (American history and culture., 2007)
Newark's volatile past is infamous. The city has become synonymous with the Black Power movement and urban crisis. Its history reveals a vibrant and contentious political culture punctuated by traditional civic pride and an understudied tradition of protest in the black community. Newark charts this important city's place in the nation, from its founding in 1666 by a dissident Puritan as a refuge from intolerance, through the days of Jim Crow and World War II civil rights activism, to the height of postwar integration and the election of its first black mayor. In this broad and balanced histor.